Application of effective microorganisms technology on dairy wastewater treatment for irrigation purposes - Mohamed Nabil Ali; Tahani F Youssef; Marwa M Aly; Abdelrahman G Abuzaid (Brawijaya University, 2021)
Due to the massive amounts of freshwater consumed in dairy industries, as a result, thousands of liters of wastewater were produced as one liter of milk produces 10 liters of wastewater which represents a major threat to the surrounding environment and aquatic life. The application of a promising technology called “effective microorganism (EM)” was the key solution due to its low operating cost, low technology, and eco-friendly condition. Three different effective microorganisms were used, such as Bacillus bacteria (EM1), Staphylococcus bacteria (EM2), and EM stoste + Molasses (EM3). EM1 and EM2 were isolated from the dairy wastewater by using streaking for isolation on an agar plate process, while EM3 was prepared by mixing 12 % EM stoste, 6% molasses, and 82% distilled water. A laboratory pilot consists of aeration and final settling tanks, both tanks followed by an activated carbon filter. Four trials were performed, the first trial was without any EM, the second trial was adding EM1 with a dose of 50 ml to the aeration tank, the third trial was EM2 with a dose of 50 ml to the aeration tank, finally adding EM3 with a dose of 30 ml to the aeration tank. Results showed that using Bacillus bacteria (EM1) was the most effective trial as it was effective in reducing TSS (total suspended solids), BOD (biological oxygen demand), COD (chemical oxygen demand), TN (total nitrogen), and TP (total phosphorous) concentrations by removal efficiency of 93%, 96.2%, 95.9%, 94%, and 64%, respectively which were below the limitations of the Egyptian code for reuse for irrigation purposes.